Physical map of the Treponema denticola circular chromosome. - MacDougall, J (1995)
A physical map of the Treponema denticola ATCC 33520 genome was constructed by pulsed-field gel electrophoresis and DNA hybridization. The organism possesses a single, circular chromosome of approximately 3.0 Mbp and a 2.6-kbp circular plasmid, pTD1. The physical map of the A+T-rich genome was constructed with the rare-cutting restriction enzymes AscI, NotI, and SrfI, which have 8-bp G+C-rich recognition sites. The genes flgE, tdpA, and prtB encoding the flagellar hook protein, a 53-kDa immunogenic protein, and chymotrypsinlike protease, respectively, were located on the map. This treponeme was found to have two copies of each of the rRNA genes, as has been found to be the case for both Treponema phagedenis and Treponema pallidum.